Impact of acetone (photo)oxidation on HOx production in the UT/LMS based on CARIBIC passenger aircraft observations and EMAC simulations. Issue 9 (1st May 2014) - Neumaier, M.; Ruhnke, R.; Kirner, O.; Ziereis, H.; Stratmann, G.; Brenninkmeijer, C. A. M.; Zahn, A.
Abstract Until a decade ago, acetone was assumed to be a dominant HOx source in the dry extra‐tropical upper troposphere (ex‐UT). New photodissociation quantum yields of acetone and the lack of representative data from the ex‐UT challenged that assumption. Regular mass spectrometric observations onboard the Civil Aircraft for the Regular Investigation of the atmosphere Based on an Instrument Container (CARIBIC) passenger aircraft deliver the first representative distribution of acetone in the UT/LMS (UT/lowermost stratosphere). Based on diverse CARIBIC trace gas data and non‐observed parameters taken from the model ECHAM5/MESSy for Atmospheric Chemistry, we quantify the HOx source in the UT/LMS from (photo)oxidation of acetone. The findings are contrasted to HOx production from ozone photolysis, overall the dominant tropospheric HOx source. It is shown that HOx production from acetone (photo)oxidation reaches up to 95% of the HOx source from ozone photolysis in autumn in the UT and on average ~61% in summer. That is, acetone is a significant source of HOx in the UT/LMS.